SISTEM PENJAMINAN MUTU: EVALUASI KESESUAIAN STANDAR MUTU DENGAN AKREDITASI INTERNASIONAL UNTUK PELAMPAUAN SN DIKTI di UIN SUNAN KALIJAGA YOGYAKARTA - Rohyanti Zulaikha, Sri; Irsyadunnas, Irsyadunnas; Rohmad Wahyudi, Muhammad Didik; Al Rasyid, Dwiyan (Jurnal Penjaminan Mutu, 2023)
Abstract This study discusses quality standards and international accreditation, with the aim of knowing how the conformity of quality standards with international accreditation exceeds SN DIKTI. SPMI implementation at UIN Sunan Kalijaga Yogyakarta uses the PPEPP cycle. The standard improvement cycle is carried out if the standard has been reached or the realization exceeds the standard. Standard improvement carried out by UIN Sunan Kalijaga Yogyakarta in 2020 by adding main performance indicators/IKU and additional performance indicators/IKT with reference to international accreditation agency standards, namely FIBAA, AUN-QA, AIQA, ABET, ASIIN and ASIIC, as well as SNPT, SPM-PT, BAN-PT which refers to 9 criteria and ISO 9001:2015. This research is a qualitative research using in-depth interview techniques, observation and documentation to find out the suitability of Quality Standards with International Accreditation for exceedance of SN DIKTI. Respondents in this study were quality standard controllers at UIN Sunan Kalijaga Yogyakarta. Qualitative data were analyzed using Miles and Huberman Interactive Model which includes data reduction, data display, and drawing and verifying. The results of the study show that there are statements in the Quality Standards that are in accordance with International Accreditation for exceeding SN DIKTI. The implementation of SPMI at UIN Sunan Kalijaga Yogyakarta has surpassed SN-DIKTI and brought international competitiveness in effective quantity and quality to develop a culture of quality, shown in the existing IKT. For example, the IKT Quality Standards of UIN Sunan Kalijaga show international competitiveness, namely UIN Sunan Kalijaga Yogyakarta has curriculum development guidelines that contain graduate profiles, learning outcomes that refer to KKNI, study materials, curriculum structure and RPS that refer to SN-DIKTI and benchmarks on international institutions, current regulations, and sensitivity to current issues, where in the IKT statement, CP refers to FIBAA, ASIIN, AUN-QA, AIQA and IABEE certification/accreditation criteria.